Natural Compounds against Neurodegenerative Diseases: Molecular Characterization of the Interaction of Catechins from Green Tea with Aβ1–42, PrP106–126, and Ataxin‐3 Oligomers. Issue 42 (1st September 2014) - Sironi, Erika; Colombo, Laura; Lompo, Angela; Messa, Massimo; Bonanomi, Marcella; Regonesi, Maria Elena; Salmona, Mario; Airoldi, Cristina
Abstract: By combining NMR spectroscopy, transmission electron microscopy, and circular dichroism we have identified the structural determinants involved in the interaction of green tea catechins with Aβ1–42, PrP106–126, and ataxin‐3 oligomers. The data allow the elucidation of their mechanism of action, showing that the flavan‐3‐ol unit of catechins is essential for interaction. At the same time, the gallate moiety, when present, seems to increase the affinity for the target proteins. These results provide important information for the rational design of new compounds with anti‐amyloidogenic activity and/or molecular tools for the specific targeting of amyloid aggregates in vivo. Abstract : Green tea for memory : By combining NMR spectroscopy, transmission electron microscopy, and circular dichroism, the structural determinants involved in the interaction of green tea catechins with Aβ1–42, PrP106–126, and ataxin‐3 oligomers have been identified. This data allows the elucidation of their mechanism of action, showing that the flavan‐3‐ol unit (see figure) of catechins is essential for their interaction.